Efficacy of Chlorantraniliprole 18.5 EC against major pests of rice - Karthikeyan, K; Christy, M M (Indian Journal of Plant Protection, 2020)
Pest management experiments were conducted during the year 2012- 2013 in two cropping seasons viz., Kharif 2012 and Rabi’2012-13 at Regional Agricultural Research Station, Pattambi using the rice cultivar, Jyothi. The insecticide molecules tested during the periods were triazophos @ (750 ml/ha and 250 ml/ha), sulfoxyflor (313 and 375ml/ha), buprofezin (800ml/ha), chlorantraniliprole (150ml/ha), acephate (660g/ha) and monocrotophos (1390 ml/ha) as check insecticide with an untreated control. The pooled results of two crop seasons revealed that chlorantraniliprole @ 150ml/ha was the most effective treatment against major rice pests like yellow stem borer, leaf folder and case worm. The grain yield per plot was also higher in chlorantraniliprole treatment.